2003
DOI: 10.1128/iai.71.4.2258-2261.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vector Priming Reduces the Immunogenicity ofSalmonella-Based Vaccines inNramp1+/+Mice

Abstract: The present studies in Nramp1 ؊/؊ BALB/c and Nramp1 ؉/؉ CBA mice question the significance of this genotype as a determinant of the level of gut colonization following oral administration of naturally attenuated or highly virulent Salmonella strains. In line with previous results in BALB/c hosts, vector priming of CBA mice with Salmonella enterica serovar Stanley was found to significantly compromise the immunogenicity of a recombinant construct expressing a foreign pilus protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Similar results were obtained in a later study (46,59), which reported that prior exposure of animals to homologous or related strains reduced the subsequent immune response in mice against the vectored foreign antigen. Finally, Attridge and Vindurampulle found that the hyporesponsiveness could be largely eliminated by exposing animals to the foreign antigen prior to vector priming (7).…”
supporting
confidence: 89%
“…Similar results were obtained in a later study (46,59), which reported that prior exposure of animals to homologous or related strains reduced the subsequent immune response in mice against the vectored foreign antigen. Finally, Attridge and Vindurampulle found that the hyporesponsiveness could be largely eliminated by exposing animals to the foreign antigen prior to vector priming (7).…”
supporting
confidence: 89%
“…The various reports are contradictory in their findings and seem to paint a rather confusing picture. Some studies concluded that pre-existing immunity against the Salmonella vector leads to stronger immune responses against the delivered antigen (Bao & Clements, 1991; Jespersgaard et al , 2001; Kohler et al , 2000a, b; Metzger et al , 2004; Saxena et al , 2009; Sevil Domènech et al , 2008; Whittle & Verma, 1997), with others considering pre-existing immunity to be a limiting factor in the long-term use of Salmonella as an efficient vector for antigen delivery (Attridge et al , 1997; Gahan et al , 2008; Roberts et al , 1999; Sevil Domènech et al , 2007; Vindurampulle & Attridge, 2003a, b). …”
Section: Effects Of Prior Immunological Exposure To Vectors – Bacterimentioning
confidence: 99%
“…However, it is important to mention that one of the disadvantages of using Salmonella as a vector for expression of heterologous antigens is the fact that previous exposure to Salmonella can significantly reduce the induction of immunity against heterologous antigens after a second challenge [145,[148][149][150]. This phenomenon is probably due to the rapid clearance of the vector by components of the adaptive immune response after a secondary infection, resulting in a reduction of the amount of heterologous antigen available for APCs [151].…”
Section: Modulation Of Immune Response By Expression Level and Cellulmentioning
confidence: 99%
“…In the case of EAE, immunization with Salmonella-CFA/I previous to EAE induction prevented demyelination and infiltration of inflammatory cells in the central nervous system. As a result, previous exposure to the recombinant Salmonella strain led to a significant reduction in the clinical score caused by challenge with the autoantigen-derived PLP (139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150)(151) peptide [182,183]. There is evidence suggesting that expansion of regulatory, FoxP3 positive T cells (Treg) is required for the induction of tolerance caused by immunization with CFA/I recombinant Salmonella, independently of autoantigen challenge [182].…”
Section: Use Of Salmonella To Induce Tolerance To Self-antigensmentioning
confidence: 99%